2019
DOI: 10.1111/grow.12311
|View full text |Cite
|
Sign up to set email alerts
|

Location matters: A spatial econometric analysis of regional resilience in the European Union

Abstract: The aim of this study is to empirically examine regional resilience by assessing economic growth patterns in two distinct groups of regions across the European Union in the aftermath of the 2008 economic and financial crisis. In an effort to consider the regions as interconnected economic areas and account for spillover effects, the model incorporates complex spatial effects that consider both spatial heterogeneity and spatial dependence. The analysis follows a step‐wise approach. First, spatial heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 80 publications
6
41
0
2
Order By: Relevance
“…Moran's I and Geary's C). While the first step of these approaches (Annoni et al, ; Bourdin, ; Longley & Tobón, ) deviates from Billé et al (); remaining effor to control for spatial mechanisms and check for coefficient stability are identical.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Moran's I and Geary's C). While the first step of these approaches (Annoni et al, ; Bourdin, ; Longley & Tobón, ) deviates from Billé et al (); remaining effor to control for spatial mechanisms and check for coefficient stability are identical.…”
Section: Resultsmentioning
confidence: 98%
“…Impact of economic turmoils can influence the regional convergence performance. Martin (), Cellini and Torrisi (); Capello, Caragliu, and Fratesi (); Cuadrado‐Roura, Martin, and Rodríguez‐Pose (); Webber, Healy, and Bristow () and Annoni, de Dominicis, and Khabirpour () highlight that regional resilience to macroeconomic turmoils is a vital element of regional growth and convergence. Our analyses so far covers the post–2000 period during which Turkey realize substantial level of economic change and development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the locational condition affects the effectiveness of industrial transformation. Experiences have shown that the better the locational condition, the less the dependence of urban economic growth on natural resources, and the more it can alleviate the “resource curse” effect, which means that metropolitan areas and high‐accessibility areas are more likely to develop alternative industries and form diversified industrial patterns (Annoni, Dominicis, & Khabirpour, ; Deng, Lu, & Xiao, ). On the contrary, the inferior location had little effect, and it even played a role in fueling its decline (Baldwin & Okubo, ; Guastella & Timpano, ).…”
Section: Introductionmentioning
confidence: 99%